Rate of growth of Pseudomonas fluorescens in donated blood. Issue 8 (August 1995) - Gibb, A P; Martin, K M; Davidson, G A; Walker, B; Murphy, W G
Abstract : AIMS–To examine how delayed refrigeration of blood affects the growth of Pseudomonas fluorescens, one of the two most important causes of sepsis resulting from transfusion of contaminated blood. METHODS–Two donations of whole blood were each divided into three aliquots and inoculated with 5-10 cfu/ml of a P fluorescens strain from a case of transfusion associated sepsis. From each donation, one aliquot was placed at 4 degrees C, one was held at 20 degrees C for six hours prior to refrigeration and the third was held at 20 degrees C for 24 hours prior to refrigeration. Samples were aseptically withdrawn over 17 days and bacterial counts were determined using a pour plate technique. RESULTS–The rate of growth of P fluorescens in blood at 20 degrees C was increased compared with blood at 4 degrees C. At 24 hours the aliquots held at 20 degrees C for six and 24 hours had, respectively, 174 and 29, 000 cfu/ml compared with 15 cfu/ml in aliquots held at 4 degrees C. There was no evidence of increased killing of P fluorescens at the higher temperature. CONCLUSIONS–These results suggest that blood for transfusion should be refrigerated as soon as possible after collection.